The Contribution Of Eye-Hand Coordination And Speed To Blocking In Volleyball Athletes Sma 5 Central Bengkulu - Efran, Efran; Sumantri, Ajis; Personi, Megi (Educative Sportive, 2025)
This study aims to determine the contribution of hand-eye coordination and speed to blocking ability in volleyball among athletes at SMA 5 Bengkulu Tengah. Using a quantitative approach, the entire population of 21 athletes was used as the sample. Data were collected through hand-eye coordination tests, speed tests, and volleyball blocking ability tests, and analyzed using correlation techniques. The results showed that both hand-eye coordination and speed had a significant influence on successful blocking. Athletes with good coordination and high speed tended to block more effectively. A normality test indicated that the data were normally distributed, thus validating the research findings. Based on these results, it is recommended that coaches place greater emphasis on improving hand-eye coordination and reaction speed in training programs.